Designing Mobile and Web-Based Damage Complaint Applications at XYZ Hospital - Niera Azzura Salma; Rini Suwartika (Jurnal E-Komtek, 2023)
A hospital is a health service place providing comprehensive individual medical services that provide inpatient, outpatient, and emergency services. Various facilities are used to support better hospital services. Facilities that are often used in hospitals are computers, laptops, printers, internet networks, and LAN networks. However, these facilities sometimes experience damage at any time, which can interfere with various activities in the hospital. In XYZ Hospital itself, damage complaints still use manual methods to make damage complaints Employees must go directly to the hospital information system division, which can cause ineffectiveness, and technicians need help handling damage complaints due to the absence of written data. This study aims to build a mobile and web-based XYZ home damage complaint application. It is expected to increase efficiency in making complaints, and technicians can more easily conduct damage complaints at XYZ Hospital.